2021
DOI: 10.3389/fpsyg.2021.684354
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of General Self-Efficacy on Psychological Resilience During the COVID-19 Pandemic: The Mediating Role of Posttraumatic Growth and the Moderating Role of Deliberate Rumination

Abstract: Purpose: This study used a moderated mediation model to explore the relationship between general self-efficacy (GSE) and psychological resilience (PR) and the associated mechanisms, the mediating role of posttraumatic growth (PTG), and the moderating role of deliberate rumination (DR) during the coronavirus disease 2019 (COVID-19) pandemic. Knowledge of the relationship between these four variables examined further understanding of the PR improvement mechanism of college students and even the general public.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 66 publications
1
28
0
Order By: Relevance
“…The present study proposed that positive gains of PTG may be correlated with the aforementioned factors from a different angle ( 23 ). Indeed, our findings are consistent with Hypothesis 2, 3, and 4 and previous studies, especially, confirming that serial mediation existed in the above relations in the context of the pandemic.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The present study proposed that positive gains of PTG may be correlated with the aforementioned factors from a different angle ( 23 ). Indeed, our findings are consistent with Hypothesis 2, 3, and 4 and previous studies, especially, confirming that serial mediation existed in the above relations in the context of the pandemic.…”
Section: Discussionmentioning
confidence: 77%
“…Nevertheless, no study has further investigated the PR improvement mechanism among college students especially in the COVID-19 background. Specifically, PR can be promoted in different ways, such as providing a supportive social network ( 68 ), elevating general self-efficacy ( 23 ), enhancing active coping self-efficacy strategies (e.g., enhancing the perception that one is able to manage or recover from a stressful event), learning mindfulness skills (e.g., deep breath and focusing on the present moment), as well as nurturing a sense of purpose in life and the ability to find meaning ( 69 71 ). According to the dimensions of PTG, traumatic events may have caused individuals to undergo positive changes and improvement in interpersonal relationships, future possibilities, personal strength, mental state, and attitudes toward life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a dynamic model of psychological resilience was jointly developed and proposed by several scientific institutions in the United States ( Mandleco, 2000 ). Both models divide the protective factors for psychological resilience into two types, internal and external ( Zeng et al, 2021 ). Internal factors include biological factors, such as physical condition, temperament, and gender, and psychological factors, such as intelligence, cognitive style, problem-solving skills, and personality.…”
Section: Theoretical Basis and Hypothesismentioning
confidence: 99%
“…Several studies have shown the COVID-19 pandemic has been associated with PTG in students that have graduated high school (Yu, Yu, & Hu, 2021) and in college students (Kutza & Cornell., 2021;Zeng, Zeng, Xu et al, 2021). However, it remains unknown whether PTG occurs in current high school students as a result of the stress experienced during the coronavirus pandemic.…”
Section: Introductionmentioning
confidence: 99%